Time remaining:
5. Please check my answer to make sure it is correct. Thanks!

label Algebra
account_circle Unassigned
schedule 0 Hours
account_balance_wallet $5

Apr 27th, 2015

Your answer is correct.


f(x) = (-5x + 2)/(x - 5)

Replace f(x) with y

y = (-5x + 2)/(x - 5)


Replace x with y and y with x

x = (-5y + 2)/(y - 5)

x(y - 5) = -5y + 2

xy - 5x = -5y + 2

5y + xy = 2 + 5x

y(x + 5) = 5x + 2

y = (5x + 2)/(x + 5)


So, f^{-1}(x) = (5x + 2)/(x + 5)


Verification Procedure:- 

If your inverse is correct

then  (fof^-1)(x) = x

Apr 26th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Apr 27th, 2015
...
Apr 27th, 2015
Jun 29th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer